Developing implementation tools for some theoretical measures for theses and dissertations in sociology: An analytical study - Mohammed, Zainab; Sachit, Khalid (Al-Adab Journal, 2025)
Methodology is a major pillar in constructing scientific studies and research, as it is one of the theoretical and applied foundations that the researcher relies on in his study as a whole, starting from determining the research topic, formulating the title, collecting scientific material, and arriving at the results. Therefore, this study sought to provide a model methodological tool to evaluate the procedures followed in writing theses and dissertations in sociology. This scale included several criteria and was used to analyze a sample of theses and dissertations from the Department of Sociology at the College of Arts at the University of Baghdad. It relied on the descriptive analytical approach. The study found that there were many problems in applying the correct methodology in the department’s theses and dissertations. The method of formulating the study problem and writing the objectives, the method of defining concepts, the methodology of employing the theory, as well as selecting the sample and using the tool, formulating the study’s conclusions and recommendations, and The study reached several conclusions, as follows: Some researchers were overly biased toward one of the variables in their title and did not detach themselves from their study when formulating the research problem, and the formulation was not objective. There is a clear flaw in the standard formulation of the study’s objectives, which is consistent with and appropriate to the title, level, and type of study. There is a flaw in the systematic use of theory in most sample studies. They either developed it but did not employ it—that is, they merely presented its contents—or they did not use theory at all. Some researchers used borrowed operational definitions, and some formulated borrowed hypotheses. We also concluded our study with the following recommendations: A greater focus in teaching methodology on hypotheses, their types, how to link and test them, and their relationship to the title, objectives, and questions. A method for teaching concepts in research methods, using appropriate examples and exercises to apply them, is essential to consolidate sociology students’ understanding of how to write them. Training for students on how to employ theory in social research.